2013
DOI: 10.4081/bam.2013.3.95
|View full text |Cite
|
Sign up to set email alerts
|

Does transcutaneous electrical nerve stimulation (TENS) have a clinically relevant analgesic effect on different pain conditions? A literature review

Abstract: Transcutaneous electric nerve stimulation (TENS) is a standard therapy used in different painful conditions such as low back pain, diabetic polyneuropathy or arthrosis. However, literature reviews focusing on the effects and the clinical implication of this method in various painful conditions are yet scarce. The purpose of this literature research was to determine, whether TENS provides an analgesic effect on common painful conditions in clinical practice. Literature research was performed using three data ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
(6 reference statements)
0
8
0
Order By: Relevance
“…8) In addition, clinical experience have suggested that TENS was beneficial for acute and chronic pains with nociceptive, neuropathic or musculoskeletal origin. 6,11) Large meta-analyses also suggested the positive outcomes for the relief of musculoskeletal and post-operative pain. [70][71][72] Moreover, a number of basic scientific researches so far demonstrated the neurophysiological …”
Section: The Clinical Effects Of Tensmentioning
confidence: 99%
See 2 more Smart Citations
“…8) In addition, clinical experience have suggested that TENS was beneficial for acute and chronic pains with nociceptive, neuropathic or musculoskeletal origin. 6,11) Large meta-analyses also suggested the positive outcomes for the relief of musculoskeletal and post-operative pain. [70][71][72] Moreover, a number of basic scientific researches so far demonstrated the neurophysiological …”
Section: The Clinical Effects Of Tensmentioning
confidence: 99%
“…It can be even selfadministered by the patients after a short instruction and individually titrated by themselves according to the analgesic response to the given electrical stimuli. 6) While previous meta-analyses and reviews supported positive outcomes for the relief of various musculoskeletal and post-operative pains, many systematic reviews regarded them to remain inconclusive. 4,[7][8][9][10] However, it was indicated that while some studies included in previous reviews were the randomized controlled clinical trials on TENS, but most studies had the methodological weakness like small sample sizes and possibility of underdosing stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the general literature, it has been difficult to test TENS efficacy in patients with neuropathic pain because trials have a low fidelity associated with inadequate TENS technique and infrequent treatments of insufficient duration (Johnson and Bjordal, 2011). However, Naka et al (2013) in their systematic review highlight that most studies revealed an analgesic effect in various painful conditions, confirming the usefulness of TENS in clinical practice. Massage is asserted to be effective in inducing relaxation and reducing challenging behaviours in persons with intellectual disabilities (Chan and Tse, 2011).…”
Section: Physical Techniquesmentioning
confidence: 99%
“…There are numerous studies on pain relief through TENS, which have reached different results. Systematic review studies examining the impact of TENS on acute pain have not obtained identical results and, to date, there is no general consensus in this regard, such that a number of authors have supported TENS, but others have dismissed it (18)(19)(20)(21). In Iran, several studies have been done into the effect of TENS on acute pain control (postcesarean pain, pain during the insertion of peripheral venous catheter, burn dressing change, and subcutaneous injection pain) (22)(23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%